Information Sharing Among Banks About Borrowers: What Type Would They Support? - Iván Major (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
I address the following issue in this paper: how does information sharing among banks about borrowers affect banks' competition, and ultimately, the interest rate borrowers pay for the loan they take? One would expect that full information sharing among banks reduces lenders' risk and results in lower lending rates than any other arrangement. This may be the reason why regulators of the banking industry would like to see full information sharing in most countries. I shall show below that the regulators' expectation is usually not fulfilled. Full information sharing will result in higher lending rates than any other form of information sharing under fairly general conditions. Despite its lucrative features, banks are not always keen on supporting full information sharing. Information sharing only about bad borrowers is the fully rational banks' dominant strategy if the proportion of bad borrowers is substantial. Myopic banks would opt for no information sharing if the proportion of bad borrowers is large. Fully rational banks would only choose full information sharing if the share of bad borrowers is small. Borrowers with good credit records, on the other hand, would prefer information sharing only about bad customers rather than full or no information sharing, for they pay lower interest rates under a black list than with any other form of information sharing or with no information sharing.
Keywords: D81; D82; D92; G21; 330; Risk and uncertainty; Credit markets; Asymmetric information; Firms' inter-temporal choice; Banks; Financial institutions; Kreditgeschäft; Informationsverbreitung; Bank; Preiswettbewerb; Kreditzins; Asymmetrische Information